Hal-Hal Yang Ada Hubungan Dengan Gangguan Pendengaran Pada Pekerja Di Beberapa Lokasi Di Wilayah Indonesia Periode Tahun 2014 Sampai Dengan Tahun 2021 - Mahmuddin, Husna Fitria; Selomo, Makmur; Abidin, Reza Zainal (Fakultas Kedokteran Universitas Bosowa, 2024)
Noise induced hearing loss is hearing loss caused by exposure to noise that is quite loud for a long period of time and usually caused by the noise of the work environment. It’s deafness is sensorineural cochlear deafness and generally occurs in both ears. The purpose of this study was to find out things that have to do with noise induced hearing loss in workers in several locations in Indonesia. The research method is an analytical research by synthesizing the results obtained from ten scientific research journals with cross sectional design. The results of the ten studies analyzed showed that there are things that have a relationship with noise induced hearing loss in workers in several locations in Indonesia period of 2014 to 2021, namely there is a significant relationship between working period (p value 0.000), noise intensity (p value 0.000), use of hearing PPE (p value 0.000), hypertention (p value 0.005) and there was no significant relationship between age (p value 0.057) and diabetes mellitus (p value 0.330) on the incidence of noise induced hearing loss in workers. The conclusion is that the incidence of noise induced hearing loss in workers in several locations in Indonesia has a significant relationship with working period, noise intensity, use of hearing PPE and hypertention, and has no significant relationship with age and diabetes mellitus